Vaccination Status and Incidence of COVID-19 among Medical Student - Kharisma, Dayu Swasti; Utami, Meita Dwi; Nabila, Audia Nizhma; Asshidqy, Muhammad Hafidz (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2023)
Background: COVID-19 (Coronavirus disease 2019) is an acute respiratory infection caused by SARS-COV-2 (Severe Acute Respiratory Syndrome Coronavirus 2). The spread of COVID-19 took place quite quickly and occurred in various countries around the world. Prevention mechanisms that need to be implemented include vaccination. The purpose of this study was to find out the different proportion of COVID-19 incidence in groups of respondents with different vaccination status. Method: This research is an analytic study with a cross sectional design. Data was taken with a questionnaire that was collected by google form. Result: Out of 112 respondents who met the inclusion criteria, the most gender was female (73.2%), the most age group was 20 years (64.3%), most of respondents had received the COVID-19 vaccine more than or equal to 2 times (75.9%) and most of the respondents had never suffering from COVID-19 (52.7%). There is a different proportion of incidents of COVID-19 from each group that received the COVID-19 vaccine less than or equal to 1 dose and more than or equal to 2 doses with a p-value 0.000. Conclusion: There is a difference proportion of COVID-19 incidence between two groups that received the COVID-19 vaccine less than or equal to 1 dose and more than or equal to 2 doses. The incidence of COVID-19 was less in the fully vaccinated group.